(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
the monetary authority in Iraq has realized a noticeable decline in inflation rates over the period 2007-2010 . this remarkable achievement is due to lasting efforts made by this authority , mainly through a permanent intervention of the Iraqi central bank in the foreign exchange market . the official intervention consists in selling foreign exchange (dollars) and buying domestic currency (dinars) with purpose of withdrawing part of money supply and raising the value of dinars VS dollars . A significant appreciation in the nominal exchange rate of domestic currency can help to decrease the price of imported goods and services and lead to dampen imported inflation . However, the actions of monetary authority seeking to push up the nominal nation’s currency don’t necessarily accord with economic fundamentals . in other word , this action puts emphatically upward pressure on the domestic currency or downward pressure on the foreign currency . in responding to continuous strategy to depreciate the foreign currency (dollars) in the official market , there has been not only movement in the exchange rate of the domestic currency in undesirable level but also an excessive demand on the foreign currency from the market players , specially banks and speculators which result in an important depreciation in the value of the nation’s currency along with high inflation rate